Monoclonal Antibodies for COVID-19 Treatment: Is It an Option in Indonesia? - Alvina Widhani (Acta Medica Indonesiana, 2023)
More than three years after Coronavirus disease 2019 (COVID-19), an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-COV2), was declared pandemic by World Health Organization, report of COVID-19 hospitalization and death have been decreasing. Even though COVID-19 as global health emergency has been declared end, research in finding and evaluating modalities that can decrease severity and mortality from COVID-19 infection are still on going.Until now, there have been more than 380,000 publications in Pubmed with search term “COVID 19”. Excessive inflammatory activation is an important part of COVID-19 pathogenesis which can be caused by interactions of the virus with the host and modulation of host immune response.2 Better understanding on COVID-19 pathogenesis could improve the strategies to manage COVID-19 infection.  Monoclonal antibody is one treatment modality that can be used to target the virus itself or modulate dysregulated immune response in COVID-19.  Monoclonal antibodies (mAbs) can halt progression of COVID-19 in high-risk patients. However, considering the limited production and high cost, is this treatment modality an option in Indonesia?